Changes in Chinese early adolescents’ group orientation and mental health from before to during the COVID-19 pandemic - Han, Xianguo; Xia, Yanyu; Yang, Panpan; Li, Dan; Ding, Xuechen; Zhang, Rongwei; Zhang, Minghao (Frontiers in Psychology, 2023)
Adolescence is a critical period for formulating and developing value orientations. The COVID-19 pandemic has dramatically restricted people’s lives, potentially leading adolescents to reevaluate what they prioritize in life (i.e., their values) and affecting their mental health. Previous studies suggest that Chinese early adolescents’ group orientation is negatively associated with mental health more strongly in rural than in urban, whereas this rural–urban differs may vary after the outbreak of the pandemic. To examine potential changes in group orientation, mental health, and their associations during the pandemic, two cross-sectional surveys of ninth-grade students in the same three school were conducted in rural and urban China in 2019 and 2021. The results showed that compared with students before the pandemic (2019, N = 516, 48.8% girls, Mage = 14.87 years), students during the pandemic (2021, N = 655, 48.1% girls, Mage = 14.80 years) displayed lower group orientation such as group responsibility and rule abiding of rural students, and higher loneliness and depressive symptoms. Social equality, group responsibility and rule abiding were all significantly negatively associated with loneliness and depressive symptoms. Those negative associations were stronger in the urban regions than in the rural region. Follow-up invariance analysis revealed that this rural–urban difference in the relations between social equality, group responsibility, and rule abiding and mental health problems was only significant during (and not before) the pandemic. The protective effect of group orientation on mental health seems to be weakened only in rural contexts. The results suggest that significant changes in macrolevel contexts may play an important role in shaping adolescents’ value orientation and mental health.